CHANGE OF THE RESERVOIR FLUID CHARACTERISTICS IN WEST SILERI SECTION, DIENG GEOTHERMAL FIELD - Hidayat, Ryan
Dieng geothermal field is a volcanic hydrothermal water dominance, lies at Wonoboso, Banjarnegara and Pekalongan District, Central Java. The study was conducted on four wells, those are RH-1, RH-2, RH-3 and RH-4 on Sileri reservoir. Change in reservoir charcteristics is indicated by comparing the condition of the past and the present conditions. The past condition is show by the occurrence of alteration minerals analyzed by megaskopis, petrographic and XRD. The present condition obtained from measurement of temperature and pressure curve and water chemistry discharge from RH-1 and RH-3 wells. Reservoir fluid evolution started with water rock interaction at temperatur 300°C. Afterwards, boiling process took place which led to the formation of the vapour reservoir at temperature 300-335°C.